HUBUNGAN ANTARA PELAYANAN ASUHAN ANTENATAL DAN FAKTOR RISIKO TERHADAP KEMATIAN PERINATAL DI PUSKESMAS KOTA PALEMBANG - Rosmiarti Rosmiarti; Enderia Sari (Masker Medika, 2013)
Childbirth is one of the factors that influence perinatal mortality. In addition to otherfactors such as the deliveries performed at home with traditional personnel as birthattendants, as well as the mother condition during pregnency are less favorable ( lessnutritional status, complications of pregnancy) and late referral. Service qualitiy is aprerequisite in order to increase the use of service need to be preceded by improvedmedical standards through the efforts of Maternal Perinatal Audit (AMP).This study aims to find out is there any relation between antenatal care services and riskfactors of perinatal death in public Health Centers of Palembang City. This study is aretrospective observation of events that already exist using a case control study usingprimary data obtained from direct interview of the respondents who visited the publichealth center by using a questionnaire, as well as secondary data source that is originatednd medical records of ANC history and outcome of pregnancy and childbirth. The resultsshowed that of 180 respondents, 75% control and 25% of cases, 71.1% receivedunstandarized antenatal care, 80.6% was not risky age, risky parity 56.7%, 68.9% ofhighly educated, and 89,4% do not experience complications in pregnancy and childbirth.The result of logistic regression analysis showed significant effect between the antenatalcare services jointly (simultaneously) on perinatal mortality in the city of palembang in2012, with age variable with complications of pregnancy and childbirth as interactionvariables. Respondents who received antenatal care services that unstandarized to havea risk 3.89 times for infants experiencing perinatal death when compared to respondentswho receive standarized antenatal care services. By knowing the relationship betweenantenatal care services and risk factors of perinatal death, it is recommended thatadequate maternal health practices, the frequency of regular visits, service providersaccording to the standar (ST) remains an effort that should be improved, needs to domore intensive counseling, and need consider improving the quality of antenatal care,especially for pregnant women with high risk and the risk of pregnancy and childbirthcomplications.